Long noncoding RNA GAS5: a novel marker involved in glucocorticoid response. - Lucafo, M; De Iudicibus, S; Di Silvestre, A; Pelin, M; Candussio, L; Martelossi, S; Tommasini, A; Piscianz, E; Ventura, A; Decorti, G (Curr Mol Med, 2015)
Glucocorticoids (GCs) exert their effects through regulation of gene expression after activation in the cytoplasm of the glucocorticoid receptor (GR) encoded by NR3C1 gene. A negative feedback mechanism resulting in GR autoregulation has been demonstrated through the binding of the activated receptor to intragenic sequences called GRE-like elements, contained in GR gene. The long noncoding RNA growth arrest-specific transcript 5 (GAS5) interacts with the activated GR suppressing its transcriptional activity. The aim of this study was to evaluate the possible role of GAS5 and NR3C1 gene expression in the antiproliferative effect of methylprednisolone in peripheral blood mononuclear cells and to correlate the expression with individual sensitivity to GCs. Subjects being poor responders to GCs presented higher levels of GAS5 and NR3C1 in comparison with good responders. We suggest that abnormal levels of GAS5 may alter GC effectiveness, probably interfering with the mechanism of GR autoregulation.
Keywords: Adult; Cell Proliferation; Female; Gene Expression Regulation; Glucocorticoids; Humans; Leukocytes, Mononuclear; Male; Methylprednisolone; Middle Aged; Receptors, Glucocorticoid; RNA, Long Noncoding; Transcription, Genetic